An analysis of motivating factors in 1,725 worldwide cases of mass murder between 1900-2019 - Brucato, Gary (The journal of forensic psychiatry & psychology, 2023)
Mass murder, particularly mass shootings, constitutes a major, growing public health concern. Specific motivations for these acts are not well understood, often overattributed to severe mental illness. Identifying diverse factors motivating mass murders may facilitate prevention. We examined 1,725 global mass murders from 1900–2019, publicly described in English in print or online. We empirically categorized each into one of ten categories reflecting reported primary motivating factors, which were analyzed across mass murderers generally, as well as between U.S- and non-U.S.-based mass-shooters. Psychosis or disorganization related to mental illness were infrequently motivational factors (166; 9.6%), and were significantly more associated with mass murder committed using methods other than firearms. The vast majority (998, 57.86%) of incidents were impulsive and emotionally-driven, following adverse life circumstances. Most mass murderers prompted by emotional upset were found to be driven by despair or extreme sadness over life events (161, 16.13% within the category); romantic rejection or loss, or severe jealousy (204, 20.44% within the category); some specific non-romantic grudge (212, 21.24% within the category); or explosive, overwhelming rage following a dispute (266, 26.65% within the category). Results suggest that policies seeking to prevent mass murder should focus on criminal history, as well as subacute emotional disturbances not associated with severe mental illness in individuals with poor coping skills who have recently experienced negative life events.